2015
DOI: 10.1039/c5ra20771a
|View full text |Cite
|
Sign up to set email alerts
|

Towards graphane field emitters

Abstract: Here we report on the improved field emission performance of graphene foam (GF) following transient exposure to hydrogen plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…This is because hydrogen atoms donate electrons to the structure, shifting the Fermi level by up to 0.25 eV. Similar results have been reported in the experimental literature, where the work function of hydrogenated carbon is decreased [27,28].…”
Section: Work Function Of Defective Graphenesupporting
confidence: 87%
“…This is because hydrogen atoms donate electrons to the structure, shifting the Fermi level by up to 0.25 eV. Similar results have been reported in the experimental literature, where the work function of hydrogenated carbon is decreased [27,28].…”
Section: Work Function Of Defective Graphenesupporting
confidence: 87%
“…To confirm the SEM observation of no damage on the steel substrate, profiler scans were taken and interferograms were constructed which are presented in Supplemental Information Figure S3 . In stark contrast, other state of the art GO based coatings were observed to show significant wear in the range of 1–30 × 10 −6 mm 3 /N m 25 , 33 , 34 on the discs. The estimated Archard wear rate for the respective counterface balls in both ambient and dry N 2 conditions shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…On the other hand, layer level encapsulation/composites have also been demonstrated to be equally effective. Zhang et al 25 have demonstrated the lowering of friction by developing a hybrid MoS 2 –rGO structure via chemical synthesis route. Friction recorded against a metal matrix composite with the hybrid lubricant and commercial alumina ceramic ball was in the range of 0.21–0.35 over a broad range of temperatures.…”
Section: Introductionmentioning
confidence: 99%